Leadership stability in Army Reserve component units - Lippiatt, Thomas F., 1940-; Polich, J. Michael (Rand Corporation monograph series., 2013)
Stability of personnel is highly valued in all military forces, especially in units that are preparing for deployment. A particular concern is personnel turbulence (personnel leaving the unit and being replaced by others) among the unit leadership. Even if the Army must live with turbulence among the bulk of unit members, it would prefer to have unit officers and noncommissioned officers in place to plan and oversee training of the troops with whom they will deploy. This monograph reports results of a study to determine the level of turbulence among unit leadership and to address several related questions: What causes leader turbulence? What effects might it have on training and preparation for future missions that may require RC units? What steps, if any, could be taken to mitigate it? The authors used data from 2003 through 2011 on Army National Guard infantry battalions and Army National Guard and U.S. Army Reserve military police and truck companies. They find high rates of personnel instability, caused generally by vacancies, personnel losses, and those who don't deploy. This turbulence generates a large influx of new leaders entering units who have not been through all the training with the soldiers they will lead. The monograph makes recommendations for estimating preparation time for different types of units and for department policy to mitigate effects on mission preparation.